2018
DOI: 10.1590/2317-1782/20182018027
|View full text |Cite
|
Sign up to set email alerts
|

Identificação das alterações de deglutição: percepção de pacientes com doenças neurodegenerativas

Abstract: RESUMO Objetivo Verificar a percepção de indivíduos com doenças neurodegenerativas quanto às alterações de deglutição, e conhecer as sensações ao deglutir que podem favorecer a identificação precoce de disfagia. Método Trata-se de um estudo transversal com 44 sujeitos com doenças neurodegenerativas. Todos responderam a um questionário para investigação da sensação percebida ao deglutir e mensuração da intensidade da sensação. Foram questionados quanto à presença de fadiga por meio da Fatigue Severity Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
(16 reference statements)
0
3
0
6
Order By: Relevance
“…47,48 The FOIS is validated in 302 acute stroke patients and used recently to classify the oral intake of MS participants. 49…”
Section: Non-instrumental Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…47,48 The FOIS is validated in 302 acute stroke patients and used recently to classify the oral intake of MS participants. 49…”
Section: Non-instrumental Strategiesmentioning
confidence: 99%
“…This functional standardized scale has been shown to have adequate reliability, validity, and responsiveness to detect changes over time. A recent study used the FOIS to classify the functional swallowing in patients with MS. 49 The FOIS must be evaluated for reliability, validity, sensitivity, and specificity in patients with MS before to be widely used in clinical practice and research.…”
Section: Functional Oral Intake Scalementioning
confidence: 99%
“…É importante conhecer a fisiopatologia da doença para compreender os sinais e sintomas de origem sensorial e motora das alterações da deglutição 15 . Neste estudo, identificou-se presença de risco de disfagia em 19 (25,7%) pacientes.…”
Section: Conclusãounclassified
“…Embora os sinais e sintomas de disfagia nem sempre sejam percebidos pelos indivíduos com EM, o reconhecimento dos mesmos auxilia na identificação precoce do risco de disfagia pelos profissionais de saúde minimizando ou eliminando suas complicações como desidratação, desnutrição e broncoaspiração, complicações pulmonares e óbito 15 .…”
unclassified
“…Crary et al (7) originally suggested the adult FOIS for stroke patients. Afterwards, other researchers expanded the FOIS for patients with traumatic brain injury (31, 32), head and neck cancer (33, 34), vocal fold immobility (35), vagal schwannoma resection (36), cerebral palsy (37), postsurgical dysphagia (38), neurodegenerative diseases (39), postextubation dysphagia in children (40), and neurogenic dysphagia (41). The FOIS for infants suggested in the present study was a simplified scale with levels reduced from 7 to 5, without taking into account the concepts of single/multiple consistency food, special preparation or compensation, and food restriction.…”
Section: Study Limitationsmentioning
confidence: 99%